Dosimetric predictors of pneumonitis in locally advanced non-small cell lung cancer patients treated with chemoradiation followed by durvalumab. (August 2022) - Gao, Robert W.; Day, Courtney N.; Yu, Nathan Y.; Bush, Aaron; Amundson, Adam C.; Prodduturvar, Pranitha; Majeed, Umair; Butts, Emily; Oliver, Thomas; Schwecke, Anna J.; Moffett, Jenesse N.; Routman, David M.; et al.
Highlights: In this real-world PACIFIC experience, the rate of grade 2+ pneumonitis is 26.3%. The rate of grade 3+ and grade 5 pneumonitis is 8.9% and 2.1%, respectively. Multiple lung and heart dosimetric parameters are predictive of pneumonitis. Overall survival at 1- and 3-years is 87.4% and 60.3%, respectively. Abstract: Objectives: The incidence and predictors of pneumonitis for patients with unresectable, locally advanced non-small cell lung cancer (NSCLC) in the era of consolidation durvalumab have yet to be fully elucidated. In this large single institution analysis, we report the incidence of and factors associated with grade 2 + pneumonitis in NSCLC patients treated with the PACIFIC regimen. Materials and methods: We identified all patients treated at our institution with definitive CRT followed by durvalumab from 2018 to 2021. Clinical documentation and imaging studies were reviewed to determine grade 2 + pneumonitis events, which required the following: 1) pulmonary symptoms warranting prolonged steroid taper, oxygen dependence, and/or hospital admission and 2) radiographic findings consistent with pneumonitis. Results: One-hundred ninety patients were included. The majority received 60 Gray (Gy) in 30 fractions with concurrent carboplatin and paclitaxel. Median number of durvalumab cycles received was 12 (IQR: 4–22). At a median follow-up of 14.8 months, 50 (26.3%) patients experienced grade 2 + pneumonitis with a 1-year cumulative incidence of 27.8% (95% CI: 21.9–35.4). Seventeen (8.9%) patients experienced grade 3 + pneumonitis and 4 grade 5 (2.1%). Dosimetric predictors of pneumonitis included ipsilateral and total lung volume receiving 5 Gy or greater (V5Gy), V10Gy, V20Gy, V40Gy, and mean dose and contralateral V40Gy. Heart V5Gy, V10Gy, and mean dose were also significant variables. Overall survival estimates at 1 and 3 years were 87.4% (95% CI: 82.4–92.8) and 60.3% (95% CI: 47.9–74.4), respectively. Conclusion: We report a risk of pneumonitis higher than that seen on RTOG 0617 and comparable to the PACIFIC study. Multiple lung and heart dosimetric factors were predictive of pneumonitis.